Sustentabilidad del cultivo de maíz en la zona de Ventanas - Álvarez Romero, Williams Fernando (2019)
One of the environmental concerns related to agricultural development is the sustainability of crops. They are closely linked with the economic, social and environmental impact for the good development of the plantation so that the product is sustainable or sustainable over time. The cultivation of corn occupies the second place as a product of mass consumption and cereal of greater consumption after wheat, adapting to different agroecological and edaphic conditions; It has also been characterized of vital importance for its multiple benefits such as for human food and industrial development. In addition, all products that are environmentally safe, socially fair and profitable can be called “sustainable” and that can be maintained over time. For the preparation of this practical document, a survey was carried out on ten corn producers in the Ventanas area. The surveys consisted of ten closed questions, the same ones that were tabulated by Microsoft Excel and diagrammed with column charts. In addition, information was collected from books, magazines, newspapers, scientific articles, papers, conferences, web pages, which was submitted to the analysis, synthesis and paraphrase technique on the level of sustainability of corn cultivation. Based on the conclusions presented, it was determined that the majority of farmers do not use adequate technology, which has an impact on yields, affecting the sustainability of corn cultivation in the Ventanas area; The requirement to achieve sustainability is the balance between the natural and social system, mutually affecting the environment and society and sustainability implies substantial changes in the scientific paradigms of all related sciences and in the actors involved in their realization.